Observation of toroidal Alfvén eigenmode excited by energetic electrons induced by static magnetic perturbations in the EAST tokamak. (22nd August 2018) - Chu, N.; Sun, Y.; Gu, S.; Wang, H.H.; Hu, Y.J.; Shi, T.H.; Chen, D.L.; Gu, X.; He, K.Y.; Jia, M.; Lin, S.Y.; Liu, H.Q.; et al.
Abstract: A toroidal Alfvén eigenmode (TAE) excited by barely trapped energetic electrons during the application of a static magnetic perturbations (MPs) is observed for the first time in tokamak ohmic heating plasmas. This TAE appears when the current of a static n = 2 MPs exceeds a threshold value, at which a forced n = 2 magnetic reconnection happens. Here, n is the toroidal mode number. This TAE is located near the plasma edge, which agrees with the calculation of the TAE gap. It propagates in the ion diamagnetic direction and has a dominant toroidal mode number n = 2. The frequency of the TAE is consistent with the precessional frequency of the barely trapped energetic electrons with energy around 150 keV. An increase of the hard x-ray emission intensity in this energy range is observed just after the n = 2 magnetic reconnection. The energetic electrons may be accelerated by the magnetic islands formed after reconnection. The TAE is stabilized after a reduction in the contents of energetic electrons. This observation suggests that the application of static MPs may provide us with a novel method to actively control Alfvén eigenmodes in fusion plasmas.